ANALISIS PENGARUH ELEMEN BRAND IMAGE, SERVICE QUALITY DAN PRODUCT QUALITY TERHADAP INDIHOME CUSTOMER SATISFACTION DI DKI JAKARTA - Rima Firmaya Sari (2023)
This study uses a quantitative method with the aim of proving the influence of Brand Image, Service Quality and Product Quality both directly and indirectly on Customer Satisfaction. This study used 100 respondents from consumers of Indihome DKI Jakarta as primary data, and secondary data researchers obtained through various references related to research. Data were collected using purposive sampling technique and analyzed using descriptive and inferential analysis techniques with the help of SmartPLS software. So that data processing obtains the results that (1) Brand Image has a positive and significant effect on Customer Satisfaction, (2) Service Quality has a positive and significant effect on Customer Satisfaction, (3) Product Quality has a positive and significant effect on Customer Satisfaction.